Les tombes romaines d'Armorique Essai de sociologie et d'économie de la mort - Galliou, Patrick (Documents d'archéologie française, 1989)
The study of the burials and cemeteries of the Roman world still suffers from an almost complete lack of regional surveys which, alone, would allow archaeologists to develop wide-ranging synthèses and a better approach of relationships between the world of the living and that of the dead. In the following work, written as a Ph. D. thesis, the author, basing his argumentation on a detailed analysis of the Roman graves discovered in the Armorican peninsula, has attempted to explore their nature and structure, and to show how, in their variety, they closely relate to the cultural diversity of the western Gaulish Civitates.